Arm function after stroke - can we make a difference? - L. Fearnhead; C. J. Eales; V. U. Fritz (AOSIS, 1999)
Impairment of upper limb function is a significant cause of functional disability after stroke. Based on a review of the literature this paper defines upper limb function and highlights some of the relevant recent developments in neuropathology. The effects of changes in sensation, muscle recruitment and tone are described. Reliable and valid outcome measures of upper limb impairment and disability are listed. The principles of rehabilitation are described in terms of timing of rehabilitation, sensory reeducation, motor control and functional use. Questions are raised regarding the need for counselling for the loss of fine discriminative hand function and for research into this behavioural aspect of upper limb rehabilitation.